AN ETHNOMATHEMATICS STUDY ON VARIATIONS OF KELARAI BUNGA TANJUNG - Wan Norliza Wan Bakar; Junaidi Awang; Mohd Saipuddin Mohd Hasbullah; Rozita Shamsuddin; Rahaidah Muhammad; Muslim Ismail (Journal of Islamic, Social, Economics and Development, 2023)
Kelarai is defined as checkered weave patterns based on the weavers’ observations of nature that inspired them to produce designs similar to it using their knowledge and skills. Few types of kelarai based on flora, fauna or abstract has been found. One of them which is unique is Kelarai Bunga Tanjung named after a creamy, white star shaped flower with white petals, which opens at twilight and gradually becoming fragrant through the night until dawn. This paper discusses An Ethnomathematics Study on Variations of Kelarai Bunga Tanjung. Various types of Kelarai Bunga Tanjung were designed. Triangulation method comprising observations, interview and analysis of kelarai used in the weaving was applied.